State accountability in maritime SAR operations involving smuggled migrants: human rights challenges at sea - Md Syful Islam; Dogara Waziri Fadason; Ali Ashraf (Discover Global Society)
Abstract This article investigates a specific and underexamined question in international law: to what extent are states legally accountable for their conduct during maritime Search and Rescue (SAR) operations involving smuggled migrants? While international frameworks such as UNCLOS, the SAR Convention, and the 1951 Refugee Convention impose clear obligations to rescue, prevent refoulement, and ensure humane treatment, these duties are frequently undermined by jurisdictional loopholes, ambiguous legal terms, and the strategic externalization of enforcement. Through doctrinal legal analysis and case studies from the Central Mediterranean, Bay of Bengal, and Caribbean Sea, the article demonstrates how states systematically reinterpret or evade these obligations to prioritize migration control over legal compliance. Unlike prior literature that treats SAR primarily as a humanitarian or logistical challenge, this study reframes it as a site of legal fragmentation and accountability failure. The article fills a critical gap by offering a structured legal critique of how state responsibility is diluted in practice. It proposes concrete legal and institutional reforms, such as binding definitions of “place of safety,” integrated SAR–asylum protocols, and regional disembarkation agreements. It argues that without legal clarity, enforcement mechanisms, and political will, SAR operations risk becoming a façade that masks violations of international protection norms.